Specification Tests of the Lucas-Rapping Model - Hart, Myra K (American Economic Review, 1987)
Aggregate fluctuations in employment and unemployment are often explained within a market-clearing framework as intertemporal substitution in labor supply. Under this hypothesis, leisure in the current period is supposed to be highly substitutable with leisure (and goods) in other periods. Consequently, labor supply responds to perceived temporary changes in the real wage although it may be inelastic with respect to permanent changes in the real wage. A very important and influential empirical study of intertemporal substitution was presented by Robert Lucas and Leonard Rapping (1969, L-R). Lucas and Rapping estimated a simultaneous equations model of the aggregate labor market under an adaptive expectations forecasting scheme and found strong support for the intertemporal substitution hypothesis. Although the adaptive expectations assumption is now rarely used in such models, the intertemporal substitution hypothesis has become quite prominent in equilibrium business cycle theories where it is used to explain how fluctuations in aggregate demand can result in real changes in output, employment and unemployment.' Besides the L-R study, relatively few attempts have been made to verify the intertemporal substitution hypothesis, and most have failed to find the kind of intertemporal substitution elasticity estimated by Lucas and Rapping.2 In addition, the L-R results have never been tested, although Joseph Altonji made some minor data corrections, extended the time period, and reproduced them.3 This paper helps to reconcile the L-R results with later findings and also provides a convincing illustration of the importance and usefulness of specification testing. Here the L-R estimates are reproduced and the model is subjected to the kind of overidentification tests now widely used in econometric analysis. The restrictions on the model are easily rejected. This standard specification testing leads to very different conclusions about the empirical importance of the intertemporal substitution hypothesis than those suggested by Lucas and Rapping.